Polar magneto-optical Kerr effect of reflected light from Graphene/InAs/Graphene/Polyimide/Al structure. (October 2021) - Roumi, Bita; Abdi-Ghaleh, Reza
Abstract: In this paper, we have numerically investigated the magneto-optical (MO) properties, and figure of merit (FOM) behavior of the reflected light from a layered structure composed of two graphene sheets, an InAs, a Polyimide, and an Aluminum layers with the arrangement of Graphene/InAs/Graphene/Polyimide/Al at the terahertz frequency region. An external magnetic field is applied to the structure along with the light propagation direction to induce the gyrotropic properties of the graphene sheets and the InAs layer. The developed 4 by 4 transfer matrix method is used to study the MO responses including the intensity reflection coefficient, Kerr rotation, and ellipticity angles spectra of the structure. At first, we compared the MO responses of the structures in the presence and absence of two graphene sheets. The results demonstrated that the performance of the structure in the presence of graphene sheets is higher than in the case without graphene sheets. To continue, the effects of applied magnetic field strength, the charge carrier density of graphene, and the InAs layer thickness have been studied for the structure with graphene sheets. The results revealed that the performance of the structure would be controlled and tuned by the investigated parameters. Highlights: We have considered a structure containing two graphene sheets and an InAs layer with an arrangement of Graphene/InAs/Graphene/Polyimide/Al. Both of the graphene sheets and the semiconductor InAs layer indicate gyrotropic characteristics under the external magnetic field. The magneto-optical responses of the reflected light from the structure have been investigated. The effects of magnetic field strength, charge career density of graphene, and InAs layer thickness on the responses of the structure have been studied.